Thrombotic microangiopathy associated with arboviral infection: Report of 3 cases. - José Luiz Coelho Júnior; Karla Cristina Petruccelli Israel; Carlos Eduardo Everton Machado; Monique Pereira Rêgo Muniz; Giuseppe Cesare Gatto; Flávio Henrique Soares Barros; Kaile de Araújo Cunha; Marcus Vinícius Guimarães de Lacerda; Precil Diego Miranda de Menezes Neves; Gyl Eanes Barros Silva (Public Library of Science (PLoS), 2021)
Dengue fever and chikungunya are viral diseases that have spread rapidly throughout the world in recent decades. The occurrence of complications is well known, including prerenal acute kidney injury (AKI), which is usually thought to be caused by dehydration and fluid loss. Thrombotic microangiopathy (TMA) is an uncommon aggravation of dengue fever and chikungunya, with only a few cases described in the medical literature. The aim of this study is to present 3 cases of TMA associated with arboviral infection. Three patients with clinical history, laboratory test, and kidney biopsy results compatible with TMA were selected for the study, 2 of whom had a serological diagnosis of dengue fever and 1 of chikungunya. The 3 patients were followed up at the Federal University of Maranhão Hospital's Nephrology Service in 2018. A targeted gene panel sequencing (TGPS) plus multiple to atypical hemolytic uremic syndrome (aHUS) multiplex ligation-dependent probe amplification (MLPA) was performed in 2 of the patients and revealed in the patient 1 a heterozygous pathogenic variant in the gene THBD, as well as heterozygous deletions in CFH, CFHR1, and CFHR3. In the patient 2, there were heterozygous pathogenic variant in the genes CFI and CFB, in addition to heterozygous deletions in the genes CFHR1 and CFHR3. Both received treatment with eculizumab and undergone recovery of renal function. The third patient had TMA not classified as either aHUS or thrombotic thrombocytopenic purpura (TTP); he abandoned the treatment and returned to the service after 2 years for a dialysis emergency. Patients with arboviral infectious disease and changes that suggest TMA should have appropriate support to establish early diagnosis and useful treatment.